The relationship between thermal management methods and hydrogen storage performance of the metal hydride tank; Journal of Materials Science & Technology; Vol. 203 - Jianhui Zhu; Xi Lin; Lijun Lv; Mingda Li; Qun Luo; Kudiyarov V. N. Victor Nikolaevich; Wei Liu; Haiyan Leng; Xingbo Han; Zhaowei Ma (2024, 2024)
Title screen